2015
DOI: 10.1177/1559827615607194
|View full text |Cite
|
Sign up to set email alerts
|

What Social, Program, and Behavioral Factors Influence the Healthy Eating Index for EFNEP and SNAP-Ed Adult Participants?

Abstract: The main objectives of this article were to determine the demographic factors, the program related factors and the behavioral factors that influence Michigan Expanded Food and Nutrition Education Program and Supplemental Nutrition Assistance Program-Education outcomes. Secondarily, we sought to understand the trends and changes in Healthy Eating Index (HEI) scores across the differing baseline score groups. The data were collected by nutrition instructors in a pretest, posttest design to capture change in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…More needs to be known about the impact on participants who start with high food literacy as evident in their self-reporting of the frequency of planning, selection, preparation and eating behaviours. Programs may operate to reinforce or confirm for participants that they are doing the right thing [51].…”
Section: Discussionmentioning
confidence: 99%
“…More needs to be known about the impact on participants who start with high food literacy as evident in their self-reporting of the frequency of planning, selection, preparation and eating behaviours. Programs may operate to reinforce or confirm for participants that they are doing the right thing [51].…”
Section: Discussionmentioning
confidence: 99%
“…Food literacy skills are developed over a person’s life and must be adapted to changing circumstances, such as moving out of home, changing household size (e.g., the birth of children), economic circumstances (e.g., changing income levels) and lifestyle factors (e.g., diagnosis of a lifestyle-related disease such as diabetes or high blood pressure). People with high food literacy attend food literacy programs [63], which suggests that programs operate more subtly to reinforce or remind participants to use their food literacy skills. The reasons that participants gave for attending FSA demonstrated that learning new ideas about cooking was the second most popular response.…”
Section: Discussionmentioning
confidence: 99%
“…31 The HEI has been previously utilized to measure EFNEP outcomes. 18,32 The relationship between EFNEP participation and diet quality has been measured 18,20,32,33 ; however, approaches have varied. Additionally, some studies explored the effect of socioeconomic factors on diet quality of EFNEP participants 32 while others focused on evaluating specific curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…18,32 The relationship between EFNEP participation and diet quality has been measured 18,20,32,33 ; however, approaches have varied. Additionally, some studies explored the effect of socioeconomic factors on diet quality of EFNEP participants 32 while others focused on evaluating specific curriculum. 20 Outcome variables also differed from one study to the other, with some assessing total HEI 32 and others focusing on nutrient intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation